2003
DOI: 10.1046/j.1365-2702.2003.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems identified in gaining non‐expert consensus for a hypothetical Wound Assessment Form

Abstract: A post-hoc analysis was carried out of a session on a wound management diploma level module that was intended to promote understanding of the complexity of wound assessment. Postregistration student nurses (n = 16) from both hospital and community settings participated in brainstorming of categories (i.e. verbatim expression) they thought should be included in a hypothetical Wound Assessment Form (WAF). Ranking of suggested categories indicated in terms of 'votes' that the most important was 'date', and the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…This investigation is part of a plan to test the extent to which personal assessor preferences might have an impact on wound assessment. It has confirmed the findings of a previous study (Maylor 2003) which indicated that where consensus does not exist on the meaning of an assessment criterion (e.g. size of wound), respondents would use additional words to justify their own description.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…This investigation is part of a plan to test the extent to which personal assessor preferences might have an impact on wound assessment. It has confirmed the findings of a previous study (Maylor 2003) which indicated that where consensus does not exist on the meaning of an assessment criterion (e.g. size of wound), respondents would use additional words to justify their own description.…”
Section: Introductionsupporting
confidence: 85%
“…This would form the basis of an item pool for future work in the development of a new method of wound assessment incorporating mapping wound progress (or otherwise) over time. On the basis of a previous study which showed that nurses use the same descriptive terms in different ways (Maylor 2003), it was judged important to attempt to find a consensus on words that all could agree were indicators of healing, stasis and deterioration. This second study is part of a sequence not only aimed to identify words that could be applied to specific wound types, but also to inform a new method of assessment to reduce the effect of assessor personality and information processing preferences.…”
Section: Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Documents such as, ‘ Record keeping—guidance for nurses and midwives ’ outline the expectation that nursing records should be clear, accurate and factual and should include details of assessments and reviews, so that information can be effectively communicated to colleagues. In an increasingly litigious society, nursing records are the first source of evidence investigated if a complaint is made and are considered legal documents. Communication and continuity of care —A WAT should enable the nurse to establish how well the wound has progressed since it was last assessed, or whether in fact the wound has become static or deteriorated as this information will inform treatment decisions . A good WAT should make this information easily available to nurses encountering a wound for the first time.…”
Section: Criteria Selection For the Optimal Watmentioning
confidence: 99%
“…In an increasingly litigious society, nursing records are the first source of evidence investigated if a complaint is made (3) and are considered legal documents. Communication and continuity of care -A WAT should enable the nurse to establish how well the wound has progressed since it was last assessed, or whether in fact the wound has become static or deteriorated as this information will inform treatment decisions (41). A good WAT should make this information easily available to nurses encountering a wound for the first time.…”
Section: Criteria Selection For the Optimal Watmentioning
confidence: 99%